Language use in new media digital communication among Iraqi interlocutors - Jabbar Anber, Sameerah; Syed Abdullah, Syed Nurulakla; Boudville, Audrey Geraldine; Yaakob, Nor Azuwan (Kuis, 2018)
Language is constructed according to distinguishable forms and rules that individuals follow and native speakers have a conceptual pattern of these rules. However, linguistic rules that shift over time have exceptions, such as the plural of woman is women, not woman. In fact,we may recognise exceptions and alter by referencing our understanding of rules shared within a language community. Through Facebook, interlocutors could share their languages that enhance their ability to manipulate communication with others. Language is an opportunity for interpersonal dialogue and the new media language of Facebook adds fuel to the linguistic fire. This study will describe the linguistic patterns of language use among 730 Iraqi members of a translator’s group in Baghdad University, specifically on Facebook and identify the mistakes through their communication. The methodology used in this study is Grice’s Maxims (1975) and the results show the participants' understanding and awareness in the adaptation of the four maxims. In summary, the group practises different language styles, dialects, and lack the use of grammatical rules and prepositions. This means that there ismisunderstanding of linguistic rules as well as frequent use of abbreviation in their speech and code-switching that leads them to resort to exercising their mother language (the Arabic language). To conclude, there is a serious lack of research on Iraqi speech via Facebook and the study ends with practical recommendations for researchers and educators